Effect of Eng-Hau medium of instruction on Upper-Basic students’ achievement in Algebra - Ajai, John Tyavbee; Iyekekpolor, Solomon A. O.; Hanawa , Herbert R. (Journal of Science and Education (JSE), 2022)
The perennial problem of poor performance of students in mathematics has made stakeholders in the education sector undertake several types of research, with diverse findings on the causes, with different recommendations for improvement. In this study Eng-Hau, a coinage for the combination of the English and Hausa languages was used to teach algebra. 244 Upper Basic School Two students in the Jalingo metropolis, Taraba state, Nigeria, were used for the study. Three research questions and hypotheses guided the study, using quasi-experimental of the non-equivalent group, involving pre-test and post-test treatment, and factorial designs. Algebra Achievement Test with a reliability index of 0.74, obtained through KR-20 formula was used for data collection. Methodology instructional packages, where algebra concepts were translated into the Hausa language were used to teach the students. Analysis of Covariance was used to test the hypotheses. Findings show that students taught using Eng-Hau performed better than those taught using the English language only. No gender disparity was found with students taught using Eng-Hau. The study also found no interaction effect of medium of instruction and gender on students’ achievement, an indication that achievement in mathematics is not based on gender, but on the medium of instruction.